Internationalization of higher education in the context of bilateral cooperation between the Republic of Kazakhstan and the Federal Republic of Germany (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the issues of cooperation between the Republic of Kazakhstan and the FederalRepublic of Germany in the field of education. Historically established ties between our countries, thepresence of the German diaspora, the desire for mutual educational, cultural and scientific exchange,predetermine the crucial importance of bilateral cooperation. The education system of Germany is widelyrecognized as one of the foremost, contributing to the resolution of the problems of modern society,the training of competitive specialists. For our state, the establishment and development of such cooperationopens up new opportunities for building an educated modern society, reforming educationalpolicies, taking into account global trends and generally accepted standards in the education system.In this regard, the main purpose of this study is to characterize the development of the process ofinternationalization of higher education in the Republic of Kazakhstan on the example of bilateral cooperationwith the Federal Republic of Germany. Based on the above stated goal, the following researchtasks were identified:– to show the role of the internationalization of higher education in the formation of highly qualified,competitive specialists on the example of bilateral cooperation of the Republic of Kazakhstan andthe Federal Republic of Germany;– to determine the patterns and principles of the internationalization of higher education in Kazakhstanand Germany;– to explore internationalization as the main trend in the development of modern world education;– supplement conceptual notions about the term «internationalization»;– to identify the main prospects for the development of the internationalization of higher education.The theoretical and methodological basis of this research was a wide range of foreign and domesticsources, regulatory documents, bilateral agreements. The research topic has a direct connection with thestate programs for the development of education, the annual messages of the President of the Republicof Kazakhstan.The practical importance of the study is determined by the possibilities of using the results obtained:in developing the strategy for the development of the university educational system, teachers, in thepreparation and development of teaching aids, in establishing various forms of international cooperationwith various states. The findings are also recommendatory for relevant organizations in addressing theproblems of the internationalization of higher education as an urgent problem, and also provide an opportunityto formulate an educational policy.Key words: internationalization of education, the international cooperation, global educationalspace, integration, globalization.